A mosquito Culex (Melanoconion) iolambdis Dyar (Insecta: Diptera: Culicidae) - Stephanie K. Larrick; Erik M. Blosser; C. Roxanne Connelly (EDIS)
EENY481, a 5-page illustrated fact sheet by Stephanie K. Larrick, Erik M. Blosser, and C. Roxanne Connelly, is part of the Featured Creatures collection. It describes this small, dark brown mosquito that exists in the tropics and subtropics and about which little is known — distribution, description, biology, medical importance, and management. Includes references. Published by the UF Department of Entomology and Nematology, August 2010.